If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -4) = 1 Reorder the terms: 4(-4 + y) = 1 (-4 * 4 + y * 4) = 1 (-16 + 4y) = 1 Solving -16 + 4y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 4y = 1 + 16 Combine like terms: -16 + 16 = 0 0 + 4y = 1 + 16 4y = 1 + 16 Combine like terms: 1 + 16 = 17 4y = 17 Divide each side by '4'. y = 4.25 Simplifying y = 4.25
| -.01X^2+.04X=-98.6 | | 3x=5x+9 | | 6-3x=4x-42 | | x^3-14x^2+47x-18=0 | | 8r+1=12-8r+5r | | 12x-16=29+2x | | (4x+1/2)=8(x+3/4) | | 3v+12=6v | | (2x-4)-12=4x-15 | | X^2+1x+1.5=0 | | -5x-8=48 | | (2x+4)-12=4x-15 | | -6h+5=5-6h | | 2z/24=6/8 | | 4x=-17 | | 2=2(x+3) | | 2x+6=6x-18 | | y-(-11)=-15 | | 15-10y=21 | | -16=x-72 | | -1+m=16 | | 13y+22=16.6 | | m-13=-8 | | y+(-18)=-37 | | 3x-(2x-6)=2 | | 3x-10x+15=20 | | 6y+12=5y | | 4x+2=10x-12 | | 8(3m-7)=32 | | -n+5+3n=15 | | y^3+49y=0 | | 4+2X-12x=0 |